2023
DOI: 10.1161/circulationaha.122.062769
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin and Left Ventricular Remodeling in People Without Diabetes: Primary Results of the EMPA-HEART 2 CardioLink-7 Randomized Clinical Trial

Abstract: Background: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have been demonstrated to promote reverse cardiac remodeling in people with diabetes or heart failure. While it has been theorized that SGLT2 inhibitors might afford similar benefits in people without diabetes or prevalent heart failure, this has not been evaluated. We sought to determine if SGLT2 inhibition with empagliflozin leads to a decrease in left ventricular (LV) mass in people without type 2 diabetes or significant heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…Notably, empagliflozin treatment also increased the frequency of circulating ALDH hi SSC low CD133 + cells previously associated with cardioprotective function. In the subsequent EMPA-HEART-2 study, conducted in individuals without T2D but with CV risk factors, empagliflozin for 6 months also induced a significant increase in ALDH hi SSC low CD133 + progenitor cells, and an increase in ALDH hi SSC mid CD163 + pro-vascular monocyte precursors and decreased ALDH hi SSC mid CD86 + CD163 − pro-inflammatory monocyte precursors [48,49 ▪▪ ,50]. This data indicated that SGLT2i therapy, independent of T2D status, mediated a beneficial increase in VR progenitor cell content.…”
Section: Lipid-lowering Agentsmentioning
confidence: 89%
“…Notably, empagliflozin treatment also increased the frequency of circulating ALDH hi SSC low CD133 + cells previously associated with cardioprotective function. In the subsequent EMPA-HEART-2 study, conducted in individuals without T2D but with CV risk factors, empagliflozin for 6 months also induced a significant increase in ALDH hi SSC low CD133 + progenitor cells, and an increase in ALDH hi SSC mid CD163 + pro-vascular monocyte precursors and decreased ALDH hi SSC mid CD86 + CD163 − pro-inflammatory monocyte precursors [48,49 ▪▪ ,50]. This data indicated that SGLT2i therapy, independent of T2D status, mediated a beneficial increase in VR progenitor cell content.…”
Section: Lipid-lowering Agentsmentioning
confidence: 89%
“…Similar findings have been observed in individuals without DM. Connelly and colleagues’ RCT showed that 6‐month treatment with empagliflozin did not significantly reduce left ventricular mass index to body surface area in individuals without T2DM and significant HF ( p = .74) 63 . The follow‐up period and sample size may be inadequate to find significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…Connelly and colleagues' RCT showed that 6-month treatment with empagliflozin did not significantly reduce left ventricular mass index to body surface area in individuals without T2DM and significant HF (p = .74). 63 The follow-up period and sample size may be inadequate to find significant changes. Given that approximately 25% of the patients in this trial had HF, we did not include it in the systematic review.…”
Section: Uncovered Evidencementioning
confidence: 99%
“…31 However, in a recent randomized controlled trial that involved patients at risk of HF, without diabetes or HF, empagliflozin did not demonstrate any significant impact on LV remodelling. 32 It has been suggested that cardiac anti-remodelling effects of SGLT2 inhibitors are particularly significant in patients with HF. 5 The DAPA-MODA study showed that dapagliflozin improved cardiac geometry by reducing LV dimensions and mass (−14%), leading to mild improvements in systolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in type 2 diabetic patients and LV hypertrophy, but not HF, dapagliflozin was associated with a reduction in LV mass 31 . However, in a recent randomized controlled trial that involved patients at risk of HF, without diabetes or HF, empagliflozin did not demonstrate any significant impact on LV remodelling 32 . It has been suggested that cardiac anti‐remodelling effects of SGLT2 inhibitors are particularly significant in patients with HF 5 .…”
Section: Discussionmentioning
confidence: 99%